A historical study of reconciliation as a challenge to the Evangelical Lutheran Church in Namibia (ELCIN) 1970-2010 - Shaanika, Eliakim (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.